Breaking the intergenerational cycle of poverty? Young people's long-term trajectories in Brazil's Bolsa Família programme - Jones, H (2017)
One of the most influential trends in antipoverty policy in recent decades has been the emergence of conditional cash transfer (CCT) programmes. CCTs seek to address poverty in the short-term through the cash benefit to meet immediate needs, and in the long-term by increasing human capital formation among poor children to break the intergenerational cycle of poverty. With their growing popularity, there has been considerable effort to evaluate CCTs' impacts; however, evaluations have been limited mostly to measuring short-term impacts. Very little is known of CCTs' long-term impacts, particularly the extent to which human capital formation among beneficiary children and young people is occurring and whether this may be contributing to changed life trajectories for them. Drawing on qualitative research with current and former beneficiaries of Brazil's Bolsa Família programme (BFP), this thesis helps to fill this gap by exploring young people's schooling and labour market trajectories and outcomes, and the implications of these for long-term, intergenerational poverty reduction. The micro-level qualitative approach taken in this research stands in contrast to the almost exclusively macro-level, quantitative evaluations that have dominated the CCT research. Such approaches are not well suited to teasing out the complex social processes that shape long-term trajectories and outcomes, nor to understanding the perspectives and experiences of young beneficiaries' themselves. This research demonstrates the importance of young beneficiaries' perspectives and experiences in understanding the long-term impacts of CCTs, as well as the social processes shaping them. This thesis makes three main contributions to the current research on CCTs. Analytically, it deconstructs and theorises the CCT model for long-term poverty reduction; empirically, it sheds light on the long-term impacts and outcomes of CCTs and the factors that influence these; and methodologically, it employs a qualitative approach that engages directly with beneficiary youth and families. The findings show that the human capital model that underpins CCTs does not hold when considering beneficiaries' long-term trajectories and outcomes. Young beneficiaries do not appear to be securing the schooling outcomes that would be consistent with changed labour market trajectories, nor do they appear to be incorporated into the labour market in ways that hold much scope for lifting them out of poverty. Rather, various structural barriers and social processes not accounted for in the BFP/CCT model – from the quality of schooling and learning, to labour market segmentation and labour supply, demand and returns; to wider structures of marginalisation –, appear to constrain young beneficiaries' opportunities to move out of poverty. The findings highlight some of the contradictions and tensions that currently exist between programme goals and structure, implementation, and outcomes. Although CCTs have contributed to important gains for the poor in various ways, their potential for facilitating long-term poverty reduction appears limited. Rather, CCTs as a policy tool for breaking the intergenerational cycle of poverty will require re-thinking the ways in which such programmes are situated within broader structures of inequality and limited opportunities that contribute to the reproduction of poverty across generations.